Milestones in water reuse : the best success stories - Lazarova, Valentina (IWA Pub., 2013)
Milestones in Water Reuse: The Best Success Stories illustrates the benefits of water reuse in integrated water resources management and its role for water cycle management, climate change adaptation and water in the cities of the future.